Jual Beli Tanah yang Belum Bersertipikat dan Pendaftarannya - Ahmad Fauzi; Arie Hardian (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The problem in this research, the transfer of rights to land that has not been bersertipikat through a purchase agreement, an effort to increase certainty and legal protection in the sale and purchase of land not yet bersertipikat, and obstacles in the registration of land rights in land sales have not certified Land. The result of the discussion that the transitional form of property rights on land that has not been certified through the buying and selling in their execution in Medan namely land that does not have a certificate, it must first be converted to make the soil based on the certificate of title for the land. After that just do buying and selling process and to the land behind the name into the name of the buyer. Legal certainty and the protection of buying and selling land that has not been certified by the lawful fulfillment of all requirements under the provisions of the applicable legislation. So that the sale and purchase of land which has not been certified to be any legal consequences in the form of delivery of the object of purchase in the form of land to the buyer as well as the submission of purchase price payment to the seller.